Production of pro-inflammatory cytokines during the early stages of experimental Paracoccidioides brasiliensis infection (2003)
ABSTRACT : Pro-inflammatory cytokines play an important role in both recruitment and activation of leukocytes migrating into tissues in response to invading pathogens. In this study the production of pro-inflammatory cytokines, determined by ELISA assays, and the recruitment of leukocytes into the lungs of BALBIc mice infected with Paracoccidioides brasiliensis conidia were evaluated during the early stages of infection. The results showed that infected mice had a significant increase in leukocytes in the lung during the first 4 days with a peak at day 2 post-challenge; infiltrates were composed mainly of polymorphonuclear neutrophils (PMN). Pro-inflammatory cytokines such as tumour necrosis factor alpha (TNF-a), interleukin (IL) 6, IL-1P and macrophage inflammatory protein (MIP) 2 were produced at elevated levels during the first 4 days post-challenge, but only in pulmonary samples and not in sera. Additionally, during the early stages of infection, overall weight loss was recorded in infected mice. These results suggest that pro-inflammatory cytokines could be responsible for the recruitment of leukocytes into the lung during the early stages of 19 brasiliensis infection. In addition, both pro-inflammatory cytokine production and leukocyte recruitment may participate in the control of infection by influencing the organization of the immune response in the host exposed to P brasiliensis conidia.